Are there work-family conflict differences between male and female employees? - Febriani, Rahmi Dwi; Triyono, Triyono; Handayani, Puji Gusri; Yendi, Fricha Meiviolona; Putriani, Lisa; Yuca, Verlanda (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
Work and family are the most important parts of human life that cannot be easily separated. Therefore, individuals must have the ability to balance their responsibilities in work and family life to become individuals with positive and loyal behavior at work. In balancing work and family, conflicts and dilemmas often arise in determining the priorities of these two things, giving rise to a situation called work-family conflict. This research aims to (1) describe employee work-family conflict based on gender (men and women), and (2) examine differences in employee work-family conflict based on gender. This research uses quantitative research methods with a comparative descriptive research type. The research sample was 100 employees of Padang State University. The research results show that there are differences in work-family conflict between male and female employees.